Recommendation of Knockdown Building Design at Yogyakarta Sand Dunes (Restricted and Heritage Areas) - Bhaskara, Adwitya; Nugraheni, Fitri; Hanafi, N. Faried (Semesta Teknika, 2019)
Sand dunes located in Special Region of Yogyakarta Indonesia is a restricted caused by the heritage and there only four spread in hemisphere one of them in Yogyakara, Indonesia. To build in sand dunes area building could not be built arbitrarily. Portable and knockdown is the character of the building that could be adjust to the conditions in Sand dunes. By the observation results compact building design with cold formed steel material for the main building material is the recommendation of this case. The design is then consulted with sub-contractors who are expert in their expertise as the validation stage, it is feasible to be transformed into a real building for the specific needs. Output of this research is recommendation of portable building model in modular form, where the design recommendation has been adjusted with building requirement in heritage and restricted area, which is also an area prone to tsunamis and wind disasters, therefore the recommended building are; easy to remove, easy to disassemble (knockdown), forward tsunami load, efficient cost and time (using cold formed steel material and prefabricated GRC), eco friendly (zero waste), does not require many workers (less man power).